SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-0246
|View full text |Cite
|
Sign up to set email alerts
|

Novel Geometry Reaching High Efficiency for Multiple Injector Concepts

Abstract: Heat losses are known to decrease the efficiency of CI engines largely. Here, multiple injectors have been suggested to shrink these losses through reduction of spray wall impingement. Studies on multiple injectors have proven the concept's heat transfer reduction but also highlighted the difficulty of using a standard piston bowl. This study proposes a two-injector concept combined with a flat bowl to reduce heat losses further. To change the spray pattern, the two injectors are injecting in a swirling motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…It is also seen that much of the combustion takes place close to the edge of the bowl, suggesting an increased heat transfer. Hot zones at the walls have been proven to increase convective heat transfer in previous studies [9,10]. A substantial portion of injector dribbling is also observed at 9-22 CAD ATDC.…”
Section: High-speed Imagingmentioning
confidence: 76%
See 1 more Smart Citation
“…It is also seen that much of the combustion takes place close to the edge of the bowl, suggesting an increased heat transfer. Hot zones at the walls have been proven to increase convective heat transfer in previous studies [9,10]. A substantial portion of injector dribbling is also observed at 9-22 CAD ATDC.…”
Section: High-speed Imagingmentioning
confidence: 76%
“…Other concepts try to utilize the chamber air volume in a better way by enhancing the mixing. For instance, multiple injectors concepts, where two or three injectors are used [7,8], have demonstrated lower heat losses as hot combustion gases are kept away from the cylinder walls with this strategy [9,10]. The multiple-injector concept is reported to directly increase engine efficiency by 1.9 %-points [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, this lower flame/wall interaction was not confirmed and needs to be studied further. Other computational studies have confirmed the heat loss reduction using multiple injectors [14,15]. In these studies, CFD simulations were performed to investigate how two injectors can reduce heat losses and increase the efficiency of an HD CI engine.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple injector concepts reduce the heat losses for compression ignition engines by low near-wall temperature gradients, a smaller wall area covered by hot gases, and reduced near-wall velocity and turbulence [8][9][10][11]. Studies suggest a 25 % heat loss reduction (at some load conditions without swirl) by placing two injectors at the rim of the piston bowl [12]. However, no study has been performed on how multiple injectors reduce heat losses at different swirl ratios.…”
Section: Introductionmentioning
confidence: 99%